The stories of four process safety legends. Issue 1 (4th February 2021) - Willey, Ronald J.; Baulch, Arthur
Abstract: In May of 2020, the editorial board of Process Safety Progress recommended that an article in the journal be dedicated to process safety legends as inspiration to others working in the field. This first article summaries the process safety career of four people: Daniel A. Crowl, Hans Pasman, Pete Lodal, and John Murphy. Combined they represent 180 years of process safety practice.